THE POSITION OF WOMAN’S POLITICAL RIGHTS IN ISLAM AND THE INDONESIAN CONSTITUTION - Dewi Dahlan (IAIN Batusangkar, 2021)
Women's political rights are often debated. Often deprived of women's rights. This is because women are often only involved in domestic or domestic matters. Basically, women's rights are the same as men's rights, including citizenship rights, education rights, opinion rights, and other rights. In connection with the position of women in obtaining political rights in the Islamic system and concept, it has been widely expressed. Some argue that Islam does not recognize political rights for women. There are those who view the same thing, there are also those who argue that Islam establishes and recognizes political rights for women except for being leaders of the state. This paper tries to describe the political rights of women in Islam and also explores the constitution of the Indonesian state. The method used is to conduct research on several literatures on politics in general regarding women's political rights and then compare them with one another.